Phloem-mobile messenger RNAs and root development - Hannapel, David J.; Sharma, Pooja; Lin, Tian (Frontiers in Plant Science, 2013)
Numerous signal molecules move through the phloem to regulate development, including proteins, secondary metabolites, small RNAs and full-length transcripts. Several full-length mRNAs have been identified that move long distances in a shootward or rootward direction through the plant vasculature to modulate both floral and vegetative processes of growth. Here we discuss two recently discovered examples of long-distance transport of full-length mRNAs into roots and the potential target genes and pathways for these mobile signals. In both cases, the mobile RNAs regulate root growth. Previously, RNA movement assays demonstrated that transcripts of StBEL5, a transcription factor from the three-amino-loop-extension superclass, move through the phloem to stolon tips to enhance tuber formation in potato (Solanum tuberosum L.). StBEL5 mRNA originates in the leaf and its movement to stolons is induced by a short-day photoperiod. Movement of StBEL5 RNA to roots correlated with increased growth and the accumulation of several transcripts associated with hormone metabolism, including GA2-oxidase1, YUCCA1a and -c, several Aux/IAA types, and PIN1, -2, and -4 was observed. In another example, heterografting techniques were used to identify phloem-mobile Aux/IAA transcripts in Arabidopsis. Movement assays confirmed that these Aux/IAA transcripts are transported into the root system where they suppress lateral root formation. Phloem transport of both StBEL5 and Aux/IAA RNAs are linked to hormone metabolism and both target auxin synthesis genes or auxin signaling processes. The mechanisms of transport for these mobile RNAs, the impact they have on controlling root growth, and a potential transcriptional connection between the BEL1/KNOX complex and Aux/IAA genes are discussed.